Challenges of having a child with congenital anomalies in Saudi Arabia: a qualitative exploration of mothers' experience - Alqarawi, Nada; Alhamidi, Sami Abdulrahman; Alsadoun, Ahmed; Alasqah, Ibrahim; Mahmud, Ilias (Frontiers in Public Health, 2023)
Background: Congenital anomalies in children lead to morbidity, mortality, or lifelong disabilities. Mothers of children with congenital anomalies face considerable obstacles in parenting their children because of their lack of knowledge about such health conditions, lack of family support, and lack of health, rehabilitation, and social care support. In Saudi Arabia, less attention is given to researching this important issue. In this context, the purpose of the study was to explore mothers' experiences and perceptions toward children with congenital anomalies. Methods: We employed a qualitative phenomenological study design. We purposively recruited 10 mothers of children with congenital anomalies from different cities in Saudi Arabia. We interviewed the mothers with an in-depth interview guideline. The interview questions were designed to explore their perception of congenital anomalies in children and their experience of parenting and seeking health, rehabilitation, education social care services for children with such anomalies. Result: Analysis of our data suggest that mothers of children with congenital anomalies face considerable challenges because of a lack of medical, rehabilitation, and social care support, lack of knowledge about these conditions and their management, lack of responsiveness of the healthcare providers, lack of support from the family and the stigma associated with such conditions. Consequently, mothers experience poor mental and social wellbeing. Conclusion: Mothers are facing considerable challenges in raising children with congenital anomalies. Regular screening for early detection of congenital anomalies, counselling support for mothers, and improving health care providers' responsiveness, knowledge, and skills are necessary. In addition, appropriate awareness-raising programs need to be implanted at the community level to counteract the stigma and negative attitudes of the community towards children with congenital anomalies and their families.